An impact of the EpiTapp® application on the quality of life of patients with drug-resistant structural focal epilepsy - E. А. Narodova; N. A. Shnayder; Е. Е. Erakhtin; V. V. Narodova (Эпилепсия и пароксизмальные состояния, 2023)
Background. One of the main goals of rehabilitation programs is to improve the quality of life (QoL) of patients with various chronic diseases, including epilepsy. However, the issues of rehabilitation of adult patients with drug-resistant epilepsy remain not fully resolved.Objective: to evaluate an impact of the author-proposed EpiTapp® method on QoL of patients with drug-resistant structural focal epilepsy (SFE).Material and methods. The study involved 60 patients with drug-resistant SFE: main group – 30 patients (median age33.5 years) with drug-resistant SFE who along with antiepileptic therapy regularly used the wrist tapping EpiTapp® method as an element of emergency self-help upon appearance of the first signs of arising epileptic seizure; control group – 30 patients (median age 39.5 years) with drug-resistant SFE who used no EpiTapp® method, but continued to receive previously selected antiepileptic therapy. QoL was assessed by the questionnaire approach using author-translated Quality of Life in Epilepsy Inventory (QOLIE-31).Results. While comparing QoL of two patient groups over a 6-month follow-up period, a significant (p<0.05) positive parameter dynamics was demonstrated only in main group but not in control group.Conclusion. The author-based EpiTapp® technique improves QoL of patients with drug-resistant SFE and can be used as an additional method of rehabilitation.